Situation Report: Hungary, 19 September 1987 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe/Radio Liberty based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. The Hungarian and Czechoslovak Prime Ministers' Meeting / by Edith Markos The New Reform Program: Where and What Is it? / by Karoly Okolicsanyi The Bank Reform: A Balance Sheet for the First Six Months / by Karoly Okolicsanyi Suicide: A Hungarian Tragedy / by Edith Markos